Malyshevа О.V. Modern studies of “civil society” in the scientific discourse of ukrainian scholars - admin, admin (Pressing Problems of Public Administration, 2019)
The modern researches of “civil society” in the scienti c discourse of Ukrainian scholars of various elds of knowledge are analyzed, the opinions of Ukrainian scholars on the functioning and development of “civil society” are presented, the conclusion about the concept “civil society” is made